A new early written Latvian source: interlinear corrections to the Latvian Lord’s Prayer in S. Münster’s Cosmography of 1552 - Kazakėnaitė, Ernesta (Baltistica, 2024)
This study presents a new source of early written Latvian – interlinear corrections to the Latvian Lord’s Prayer in the Cosmography by Sebastian Münster (1488–1552). They are found in the 1552 edition of the Cosmography in Latin, which is currently preserved at the Wroblewski Library of the Lithuanian Academy of Sciences in Vilnius. The corrections are anonymous and difficult to date, but an analysis of the language suggests that they belong to early period sources.
Keywords: early Latvian manuscripts; Sebastian Münster; Lord’s Prayer; editing